Spiritualizing politics without politicizing religion: the example of Sargent Shriver - Price, James R. (University of Toronto Press, 2022)
Frontmatter -- Contents -- Preface -- Chapter One. Religion and Politics: Doing Things Differently -- Chapter Two. The Public Faith of Sargent Shriver, 1955-1959 -- Chapter Three. Shriver on Spirituality and Politics, 1961-1964 -- Chapter Four. Explaining What Shriver Did -- Chapter Five. Religion, Politics, and the Peace Corps -- Chapter Six. The Way Forward -- Notes -- Bibliography -- Index